Pengaruh Pembelajaran Kooperatif terhadap Kecerdasan Interpersonal Siswa di MTs Muhammadiyah se Kota Pekanbaru - Sawalluddin, Sawalluddin; Emilda, Tika (Lembaga Anotero Scientific, 2022)
Interpersonal intelligence that is successfully developed well will greatly determine a person's success in life after he or she completes formal education. Cooperative Learning is a learning model that prioritizes cooperation between students to achieve learning goals. This research aims to determine the influence of cooperative learning on students' interpersonal intelligence at MTs Muhammadiyah in Pekanbaru City. This research is quantitative research in the form of correlation with data collection techniques using questionnaires and documentation. Meanwhile, the population in this study was all students in class VIII of MTs Muhammadiyah in the city of Pekanbaru. MTs Muhammadiyah 01 as many as 19 people. Meanwhile, class VIII MTs Muhammadiyah 02 had 85 people. so the total population is 104 students. This research did not take samples, meaning that the entire population was used as research respondents. Data analysis techniques using product moment correlation with the help of the SPSS 20.0 program. After carrying out data analysis using the product moment correlation formula, it can be concluded that there is a significant influence of Cooperative Learning on Student Interpersonal Intelligence at MTs Muhammadiyah in Pekanbaru City. This is proven by the probability value of 0.000>0.005, so Ha is accepted and Ho is rejected and the contribution of variable X to Y is 51.12%, and the remaining 48.88% is influenced by other variables not included in this research.